2021
DOI: 10.2298/jas2101067p
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cutting thickness, shape and moisture content on oil absorption during potato frying

Abstract: Potato chips and French fries are products which are often used in the human diet. The aim of this study was to investigate the influence of cutting thickness, shape and moisture content on palm olein uptake, as well as the quality of the palm olein during the production of fried potatoes. Blanching operation was conducted in water for 3 minutes at a temperature of 85oC, while the frying process was conducted in palm olein for 3 minutes at a temperature of 165oC. The peroxide value and free f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Some studies evaluated the effect of slice thickness and frying temperature on the colour, texture and fat absorption of chips made from white-or yellow-fleshed potato cultivars. The results of these studies showed that the above-mentioned factors influenced the physical and chemical characteristics of traditional potato chips [19][20][21][22]. This demonstrated the need for potato chip manufacturers to suitably select cultivars and processing parameters.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some studies evaluated the effect of slice thickness and frying temperature on the colour, texture and fat absorption of chips made from white-or yellow-fleshed potato cultivars. The results of these studies showed that the above-mentioned factors influenced the physical and chemical characteristics of traditional potato chips [19][20][21][22]. This demonstrated the need for potato chip manufacturers to suitably select cultivars and processing parameters.…”
Section: Introductionmentioning
confidence: 95%
“…The fat content of chips varies between 35 and 45% in total and can be 1/3 or more of the total weight [18]. According to the literature, the cultivar characteristics, slice thickness, frying temperature and time affect the absorbed fat content in potato products, such as chips [19][20][21][22]. Pedreschi et al [23] reported that frying at 120 • C produced potato chips that were crispier and contained more fat than potato chips fried at 180 • C. Paunović et al [20] also found that the slice thickness and the surface area of the potato had a significant effect on fat uptake.…”
Section: Introductionmentioning
confidence: 99%